The Influence of Explicit Instructional Learning Model on Learning Outcomes of Basic Subjects of DPIB Design of Student Information Modeling and Buildings of State Vocational High School 1 Percut Sei Tuan - Sihite, Hafni Aprilia; Sebayang, Nono; Izzadati, Zhili; Atika, Liana; Rani, Cut Meuthia (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to determine the influence of the Explicit Instruction learning model on learning outcomes of the basics of DPIB students in class x Design Modeling and Building Information in state vocational school 1 Percut Sei Tuan. This research method is a True Experimental Design with a Pretest-posttest Control Group Design. In this design, there are two groups selected at random, then given a pretest to find out whether there are differences between the experimental group and the control group in the initial situation, then a comparison of the posttest learning results of the two sample classes will be seen. Based on the research results, the use of the Explicit Instruction type cooperative learning model has a better impact on learning outcomes in the basics of DPIB cognitive in the material drawing plane shapes. This is proven by research results which show that the average cognitive and skills domain learning outcomes of students taught using the Explicit Instruction type cooperative learning model is 81.07 higher than the average learning outcomes of students treated with the Discovery Learning model, which is 67.37. This is also reflected in the research data, the t test results show at value of 1.88 compared to the t table value of 1.672 (t value > t table). Based on these differences, both theoretically and proven by statistical analysis carried out in this research, it can be concluded that the Explicit Instruction type cooperative learning model has a significantly different influence on student learning outcomes in the basics of DPIB cognitive in the drawing material. Form of field for class x students of the DPIB skills program at SMK Negeri 1 Percut Sei Tuan.